The effects of transfer laws on youth with sexual or robbery offenses - Rinehart, Jenny K. (Criminal justice and behavior, 2016)
This study examines the effects of juvenile transfer laws on youth charged with sex offenses and youth charged with robbery offenses. Using matched samples of youth charged in South Carolina between 1990 and 2001, we examined the effects of transfer on adjudication, incarceration, and recidivism. For youth charged with sex offenses, there were no significant effects of transfer on adjudication or incarceration. Transferred youth were more than 4 times as likely to be convicted of a new person offense as youth adjudicated in juvenile court. For youth charged with robbery offenses, transferred youth were less likely to be adjudicated, but when adjudicated, they were more likely to be incarcerated than those processed as juveniles. Transferred youth were also less likely to be arrested for or convicted of new nonperson offenses and less likely to be arrested for any new offenses. Implications for juvenile transfer policy and future research are discussed.